Emergence of Kebsiella pneumoniae Carbapenemase (KPC)- Producing Klebsiella pneumoniae in Infected Patients in Dr. Kariadi Hospital - ., Maryani; Damayanti, Kusmadewi Eka (Nexus Biomedika, 2015)
Background: KPC-producing K. pneumoniae are a group of emerging highly drug-resistant Gram-negative bacilli causing infections associated with significant morbidity and mortality. The emergence of KPC-producing K. pneumoniae has now become a global concern. The ability of this bacteria hydrolyzing carbapenem makes limited antibiotic choice for severe infections.Â KPC spreads through plasmid-mediated, thus this bacteria can spread rapidly. Methods: This was a descriptive research with total sampling as the sampling technique used was all the population within a period of one year in 2012. The research was done in Microbiology Laboratory, School of Medicine, Sebelas Maret University and the samples were from Dr. Kariadi Hospital. The research subject was 79 Klebsiella pneumonia isolated from all infected patients along 2012. Susceptibility test was performed for all samples with diffusion method using Mueller-Hinton and meropenem. The decreased sensitivity of the samples carried on Modified Hodge Test to determine if the bacteria produced KPC. The results of the study were analyzed using descriptive analysis. Results: From the 79 samples, 10 (12.66%) samples decreased sensitivity to meropenem. Those ten samples consisted of cases of sepsis 30%, pneumonia 20%, urinary tract infection 20%, surgical site infection 10%, diabetes mellitus wound infections 10%, and bronchitis 10%.Â From the ten samples, 60% were nosocomial infection and 30% were from ICU. It was found that one sample (1.27%) was Modified Hodge Test positive. Conclusions: This research found the incidence of KPC-producing Klebsiella pneumoniae in infection patients in Dr. Kariadi Hospital. This result can be a warning for Indonesian health considering the danger of KPC bacteria. Early identification of bacteria that produce KPC with in vitro testing is critical for the success of infection control. Keywords: Klebsiella pneumoniae, Klebsiella pneumoniae carbapenemase (KPC), Carbapenem-resistant, Modified Hodge Test.